2016
DOI: 10.14309/00000434-201610001-00014
|View full text |Cite
|
Sign up to set email alerts
|

Biliary Drainage Improves the Predictive Value of Modified Glasgow Prognostic Scores in Inoperable Pancreatic Cancer

Abstract: ObjectiveTo assess the influence of biliary drainage to cholangitis on modified Glasgow Prognostic Score (mGPS) in patients with pancreatic cancer. MethodsmGPS was calculated before and after biliary drainage in 47 consecutive patients with inoperable pancreatic cancer who were receiving chemotherapy. Biliary drainage was indicated for malignant obstructive jaundice that prevented the administration of chemotherapy. To elucidate mGPS values, serum levels of CRP and albumin were measured at the time of diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Finally, 26 studies were included in this meta-analysis. 15 - 40 The literature selection process is shown in Figure 1 . In the included studies, one study 18 recruited 2 independent cohorts of patients receiving chemotherapy or surgical resection, and the HRs and 95% CIs were separately given for these 2 cohorts.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, 26 studies were included in this meta-analysis. 15 - 40 The literature selection process is shown in Figure 1 . In the included studies, one study 18 recruited 2 independent cohorts of patients receiving chemotherapy or surgical resection, and the HRs and 95% CIs were separately given for these 2 cohorts.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 24 cohort studies consisting of 4651 patients [15][16][17][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][36][37][38][39][40] reported the HRs and 95% CIs for the relationship between mGPS and OS in pancreatic cancer. A random-effects model was applied due to significant heterogeneity (I 2 ¼ 68.1%, P < .001, Table 2; Figure 2A).…”
Section: Association Between Mgps and Osmentioning
confidence: 99%
“…Ultimately, 20 studies [8,[15][16][17][18][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] including 6512 patients were enrolled in this meta-analysis after excluding ineligible studies.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…2. In 12 studies that used mGPS=1 as the cutoff value, the subgroup analyses based on the region showed that eastern patients with higher mGPS had a decline of OS (HR=1.60, 95% CI=1 24. 2.06, P<0.0001), but not in western patients (HR=1.34, 95% CI=0.80-2.26, P=0.268; Fig.…”
mentioning
confidence: 94%
“…1, the literature search process was summarized in the ow diagram according to Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) [23]. Ultimately, 20 studies [8,[15][16][17][18][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] including 6512 patients were enrolled in this meta-analysis after excluding ineligible studies.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%